A Critical Analysis of Selected Aspects of Real Estate Taxation in the Context of Recent Legislative Amendments in the Czech Republic - Zelenská, Taťána (Review of European and Comparative Law, 2024)
The real estate tax is the sole property tax in the Czech Republic and has been part of its tax system since its establishment, i.e. since January 1, 1993. The Czech Republic has long been recommended by the Organisation for Economic Co-operation and Development (OECD) to increase the collection of this tax because its yield as a share of gross domestic product (GDP) is one of the lowest among all OECD and EU countries. The lower yield is in part attributable to the manner in which the tax base is determined. The Czech Republic, with the exception of a few minor instances, continues to employ the assessment-based rather than the value-based method of determining the tax base. Furthermore, the Czech Republic is encouraged to use the correction elements at the disposal of municipalities to influence the amount of property tax. This article examines the revenue aspect of real estate tax in the Czech Republic, including the determination of the tax base and the use of correction mechanisms. In light of these considerations, it is evident that the development of the Czech real estate tax system has been influenced by a number of factors, including the introduction of one of the most significant amendments to the Real Estate Tax Act in the country’s history. This amendment, known as the consolidation package, was implemented on January 1, 2024 and has had a profound impact on the current legislation.